DESIGN AND IMPLEMENTATION OF RIPEMD-160 HASH FUNCTION USING VERILOG HDL - Sharifah Azizah, Wan Alwi (Universiti Malaysia Sarawak, (UNIMAS), 2022)
Information security is now of the utmost importance since it aims to safeguard data that is valuable to individuals and companies thus a variety of encryption methods have been studied due to the numerous risks and vulnerabilities that computer networks have. Now, sensitive data can be safely transmitted via the network thanks to the Cryptography Algorithm's usage of encryption to safeguard data. Data is securely encrypted so that only the intended receiver can access it, which implies that the cryptography can also confirm the authenticity of the sender proving that the sender was legitimate and not an impostor. The hash function uses a mathematics conversion to inevitable “encrypt” messages to provide a digital fingerprint. Basically, it is used for message digest. RIPEMD-160 is one of the algorithms in hash function that can improve the security in storing information. This security algorithm was examined and put into use in this project using an iterative methodology. This project proposes to design an iterative method of RIPEMD-160 in order to investigate the security algorithm and its implementation. Besides that, iterative methods also used to improve the frequency, power and are requirements performance of RIPEMD-160 hash function. It is implemented using Verilog HDL software and simulated using the ModelSim software. The performance is determined by analysing the maximum frequency in which for this design is 125.25 MHz and the throughput is 631.8 Mbps.